Vierteljährliche Entstehungsrechnung des Bruttoinlandsprodukts für Ostdeutschland: Sektorale Bruttowertschöpfung - Hans-Ulrich Brautzsch; Udo Ludwig (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2002)
– Data regarding the development of macroeconomic production and employment are essential for the political decision process. Especially timely available information is a critical issue. Reliable short run data are not reported for East Germany yet. Because of data limitations for the past quarterly sectoral series of production and employment are derived from annual national accounts data using a set of indicators by branches. Indicators have been tested and cover working hours and sales, among others. For the period from 1992 to 2001 quarterly series for sectoral GDP are derived. A flash estimator for the overall macroeconomic performance is obtained through aggregation.
urn:nbn:de:gbv:3:2-20175
Keywords: 330; Wertschöpfung; Branche; Volkswirtschaftliche Gesamtrechnung; Neue Bundesländer